The effect of crop year and agrotechnical factors on the yield of various maturity groups of Limagrain maize hybirds - Bogdán, Imre (Acta Agraria Debreceniensis, 2012)
The Limagrain maize hybrids in different maturity groups were examined at the Látókép Experimental Station of the Centre of Agricultural Sciences and Engineering, University of Debrecen on a calcareous chernozem soil with loam texture, between 2001 and 2007 in a multifactorial long-term field trial. Doses of fertilizers: 1 N:0.75 P2O5:0.88 K2O fixed proportion of NPK doses. The basic dose of nitrogen is 30 kg ha-1. The application of fertilization was 1, 2, 3, 4, and 5 times more than the basic dose, beside of untreated control. The long-term field trial is performed in none irrigated and in irrigated version.The goal of the study was to analyze the effect of precipitation (environment factor) in one hand, and to evaluate the effect of fertilization and irrigation (agrotechnical factors) on the yield of maize hybrids in different maturity groups in the other hand. At the same time I studied the effect of interaction of different factors on the yield of maize. Analysis the yield of Limagrain hybrids revealed: the years considerably affected the level of the yield. In dry years the yield was 1.351 t ha-1 less, than in rainy years. As the effect of fertilization the yield increased, the statistically proved biggest increment was at level of 90 kg N ha-1. Evaluating the maturity groups, FAO 300 hybrids reached higher level of yield. In non irrigated conditions in the average of the seven years 60 kg N ha-1 was sufficient to reach the maximum yield. The efficiency of fertilization on yield in irrigated version increased, 120 kg N ha-1 assured the reliable level of yield. Without irrigation in comparison to the results of FAO 200 group, with the growth of FAO numbers the yield is increasing in all cases. The most significant increase was at FAO 300 (3.562 t ha-1). With irrigation the greatest difference in yield was in FAO 400 (+2.720 t ha-1) compared to FAO 200.